Eye Behavior Associated with Internally versus Externally Directed Cognition - Benedek, Mathias; Stoiser, Robert; Walcher, Sonja; Körner, Christof (Frontiers in Psychology, 2017)
What do our eyes do when we are focused on internal representations such as during imagination or planning? Evidence from mind wandering research suggests that spontaneous shifts from externally directed cognition (EDC) to internally directed cognition (IDC) involves oculomotor changes indicative of visual disengagement. In the present study, we investigated potential differences in the eye behavior between goal-directed forms of IDC and EDC. To this end, we manipulated the focus of attention (internal versus external) in two demanding cognitive tasks (anagram and sentence generation). IDC was associated with fewer and longer fixations and higher variability in pupil diameter and eye vergence compared to EDC, suggesting reduced visual scanning and higher spontaneous eye activity. IDC was further related to longer blinks, lower microsaccade frequency, and a lower angle of eye vergence. These latter changes appear conducive to attenuate visual input and thereby shield ongoing internal processes from external distraction. Together, these findings suggest that IDC is accompanied by characteristic eye behavior that reflects a decoupling of attention from external events and serves the gating of visual input.